The Nasal Airway: A Critical Review - Wever, Capi C. (Facial Plastic Surgery, 2016)
Functional nasal surgery is frequently performed and deeply embedded in otolaryngology. However, unequivocal proof of its efficacy is still pending, leading some health authorities toward restrictive policies. In this article, we review the evidence and suggest that reexamining the paradigm of functional nasal surgery may be appropriate.
Keywords: nasal airway obstruction; surgery; review; patient-reported outcome; objective measures